ANALISIS KETERKAITAN HARGA MINYAK MENTAH DUNIA DAN RETURN INDEKS HARGA SAHAM DOMESTIK DI 4 NEGARA EMERGING MARKET ASIA TAHUN 2009 - 2012 - , SENO BANYU AJI Y.P ([Yogyakarta] : Universitas Gadjah Mada, 2013)
World oil prices become an important issue in the economy because oil is the main energy source. In 2007 for the first time in world oil prices hitting $ 100 per barrel. The movement of oil prices is drawing public attention around the world, especially for countries with the status of net-oil importer. The increase in world oil prices feared to have a negative impact on the economy, not least on the domestic stock market. Asia's rapid economic growth after the Asian crisis, makes the domestic stock price index in Asia's emerging markets are growing rapidly. So it attract attention of many investors and analysts. The increase in oil prices and the rapid growth of the stock market interesting to study how the relationship between the two variables. The objective of this research to analyze the relationship between world oil prices and domestic stock markets in emerging markets Asia Countries. Techniques of analysis in this study using the VAR (Vector Autoregresive). Analysis tools that important of the VAR are Granger Causality, Impulse Response Function (IRF), and the Forecast Error Variance Decomposition (FEVD). The data used in this study are daily data from 1 January 2009 until 30 November 2012. Return stock price index of the countries studied are Indonesia, China, India, and South Korea. The empirical evidences indicates Granger Causality analysis on the state of China and Indonesia are unidirectional relationship of an impact world oil prices to domestic stock price index return. In the State of South Korea there are bidirectional relationship between oil prices and the domestic stock price index return. While in the State of India there is a unidirectional relationship from the domestic stock price index return affect world oil prices. Furthermore, IRF analysis reveal a positive response return of stock price index return due to rising world oil prices. Then oil prices respond positively due to increases the stock price index return. The results of the analysis conclude that the overall FEVD oil prices have a greater ability to explain changes in the stock price index return than otherwise, Except the country of India. It show the world oil prices could account for approximately 5% of the variance in change in the stock price index return. And from the analysis FEVD also known as simulated 15 periods of observation, the biggest shock comes from the variable itself. The cause of the positive responses of stock price index return due to rising world oil prices, one of the reason is because the flow of petrodollars beside that many foreign investment flow into the emerging markets country. This is because the expectations of investors in the stock markets in emerging markets remains positive despite high world oil prices due to economic growth brilliantly. Especially when these countries emerging markets Asia has many factors attract investments, the good economic performance, macroeconomic policies prudent, investment return rate is relatively high and the risk factors are relatively better. These results are consistent with research Narayan (2009) on Vietnam stock market which is also an emerging market. Using ECM models, he found a positive and significant relationship between oil prices and the stock price index in vietnam.